2016
DOI: 10.1080/08997659.2016.1206637
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Detoxifying Markers for Florfenicol in Rainbow Trout Liver

Abstract: Florfenicol (FF) is employed in fish farms to contest or prevent bacterial infections. However, this pharmaceutical may produce reactive oxygen species that may cause biochemical changes in antibiotic-treated fish. The aim of this study was to evaluate the effect of FF on Rainbow Trout Oncorhynchus mykiss treated for 10 d with 7.5 and 15 mg/kg FF followed by a withdrawal period of 5 d. Superoxide dismutase, catalase, glutathione peroxidase, glutathione reductase, glutathione S-transferase, glyoxalase I and gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 54 publications
3
5
0
Order By: Relevance
“…It has been reported that amphenicols (Memik 1975) and oxytetracycline (Julinta et al 2019) are hepatotoxic so also our study with FFC. Also, the FFC can cause an increase in the weight of the liver (Elia et al 2016). Our results con rm the ndings of Er and Dik (2014), who observed a hike in AST levels upon FFC application in Oncorhynchus mykiss.…”
Section: Discussionsupporting
confidence: 91%
“…It has been reported that amphenicols (Memik 1975) and oxytetracycline (Julinta et al 2019) are hepatotoxic so also our study with FFC. Also, the FFC can cause an increase in the weight of the liver (Elia et al 2016). Our results con rm the ndings of Er and Dik (2014), who observed a hike in AST levels upon FFC application in Oncorhynchus mykiss.…”
Section: Discussionsupporting
confidence: 91%
“…It has been reported that amphenicols (Memik 1975) and oxytetracycline (Julinta et al 2019) are hepatotoxic so also our study with FFC. Also, the FFC can cause an increase in the weight of the liver (Elia et al 2016). Our results con rm the ndings of Er and Dik (2014), who observed a hike in AST levels upon FFC application in Oncorhynchus mykiss.…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, the reduced activity of this enzyme reported in our study indicates damage to the system in phase II of the FF detoxification process, making it difficult for fish to eliminate FF from their bodies. Elia et al (2016) evaluated the effect of FF on Rainbow Trout Oncorhynchus mykiss treated for 10 d with 7.5 and 15 mg/kg FF followed by a withdrawal period of 5 d,and detected oxidative damage during the antibiotic treatment as a consequence of the effect of FF toxicity and a rise in total glutathione and glutathione S-transferase levels, even after the withdrawal period.…”
Section: Discussionmentioning
confidence: 99%